RESEARCH IMPACT: 1790 DIRECT CITATIONS - Irene Kamberidou (National and Kapodistrian University of Athens (NKUA), 2025)
Also used as ‘Start-up Research Tool and Reading List’ - recommended material and research tool for students, scholars and researchers: contains hundreds of academic / scientific papers, articles and studies globally.   ------------------------------------------------------------------- 1825 Direct citations since 2003 (updated May 16, 2025) ...... 1825  ετεροαναφορές/παραπομπές/αναφορές—απευθείας στο έργο—σε επιστημονικά περιοδικά, βιβλία, πρακτικά συνεδρίων, διδακτορικές διατριβές, μεταπτυχιακές διατριβές, κεφάλαια βιβλίων,  κ.ά. (από το 2003 έως 15/05/2025).